Trade disputes and the dispute settlement understanding of the WTO an interdisciplinary assessment - Hartigan, James C. (Emerald, 2009)
The volume is partitioned into five sub areas, addressing the process of dispute resolution and appeal under the DSU of the WTO; politics and disputes between sovereign nations; power inequities in access to the DSU; specific categories of disputes, such as in agriculture and in intellectual property; and issues pertaining to compliance, enforcement and remedies. In addition to the interdisciplinary focus, this volume showcases the thoughts of both established and emerging scholars, whilst highlighting perspectives from many different countries and regions.
Keywords: World Trade Organization -- Rules and practice.; Foreign trade regulation.; Tariff -- Law and legislation.; Non-tariff trade barriers -- Law and legislation.; Dispute resolution (Law); elektronické knihy; electronic books